KONSEP KESEIMBANGAN RANAH PENDIDIKAN DALAM KITAB TA’LIM MUTA’ALLIM: (Telaah Taksonomi Benjamin S. Bloom) - Salis Irvan Fuadi; Robingun Suyud El Syam; Ngatoillah Linaja (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
Abstract: Educational style that tends to be formalistic and only concerned with academic achievement, it is necessary to balance the cognitive, affective and psychomotor domains. With a research literature approach, it is found that the concept of education in the book of ta'lim muta'allim is actually a building of the concept of character education, which in the book covers at least three aspects, including character education to Allah, to fellow creatures and to oneself. This concept is in line with the cognitive, affective and psychomotor domains, where all three must be carried out in a balanced manner.